2022
DOI: 10.1111/bjh.18210
|View full text |Cite
|
Sign up to set email alerts
|

Can B cell‐deficient patients rely on COVID‐19 vaccine‐induced T‐cell immunity?

Abstract: Summary Anti‐CD20 antibody treatments prevent humoral responses to vaccines against severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) vaccines, but the nature of T‐cell responses in this setting is less well understood. Riise et al. assess vaccine‐induced epitope‐specific CD8 T cell responses in patients with lymphoma recently treated with rituximab and find a wide range of responses, with the most recently treated patients frequently failing to respond, while others exhibit responses str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Previous findings showed that the frequency of the MAIT cell compartment positively correlates with the anti-SARS-CoV-2 IgG levels in BNT162b2 mRNA vaccinated subjects ( 28 ). Since some SARS-CoV-2 infected or vaccinated individuals may elicit a cellular sensitization without evidence of the virus-specific Ab production ( 41 , 42 ), we performed a comparative analysis between the concentrations of anti-SARS-CoV-2 IgG and the level of the MAIT-associated TNF in our dataset. Importantly, we found an overlapping trend between these two parameters that showed the highest magnitude early after the vaccine boost in relation to their pre-vaccine status ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous findings showed that the frequency of the MAIT cell compartment positively correlates with the anti-SARS-CoV-2 IgG levels in BNT162b2 mRNA vaccinated subjects ( 28 ). Since some SARS-CoV-2 infected or vaccinated individuals may elicit a cellular sensitization without evidence of the virus-specific Ab production ( 41 , 42 ), we performed a comparative analysis between the concentrations of anti-SARS-CoV-2 IgG and the level of the MAIT-associated TNF in our dataset. Importantly, we found an overlapping trend between these two parameters that showed the highest magnitude early after the vaccine boost in relation to their pre-vaccine status ( Figure 5A ).…”
Section: Resultsmentioning
confidence: 99%
“…our 5 x 10 4 TCID 50 ), and used a variant of SARS-CoV-2 that is not pathogenic in wild type mice ( 6 ). In addition to specific antibody responses, COVID-19 vaccinees and convalescent patients possess SARS-CoV-2 specific CD8 + and CD4 + T cells, suggesting the contribution of the T cell compartment to the adaptive immunity to COVID-19 ( 29 ), and clinical findings have revealed vaccine-induced T cell responses in B cell-deficient patients ( 30 ). It has also been reported that vaccination by WA (Wuhan) Spike in a mouse model failed to produce antibodies fully capable of neutralizing the SA (Beta) variant of SARS-CoV-2, yet immunized mice were protected against Beta strain challenge ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The robust B cells and T follicular helper cell responses stimulated by COVID-19 vaccination contribute to the production of antibodies, which provide remarkable protection against SARS-CoV-2 infection, and reduction in hospitalization and death [ 13 , 14 ]. Notably, the depletion of B cells with anti-B antibodies in Non-Hodgkin lymphoma and chronic lymphocytic leukemia patients has been shown to weaken the humoral response and the production of Spike-specific antibodies following vaccination, increasing the risk of breakthrough infections [ 15 , 16 , 17 ]. Effector T and B cell responses following infection or vaccination also contribute to the subsequent development of specific immunological memory [ 18 ].…”
Section: Introductionmentioning
confidence: 99%